2015
DOI: 10.3109/00207454.2015.1077331
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of 23 cases with subacute combined degeneration

Abstract: The sensory symptoms occur earlier than the motor symptoms in SCD patients. SCD patients may have sensory deficit level. Normal or even elevated serum levels of vitamin B12 may occur in patients with SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…In this case, serum methylmalonic acid and homocysteine levels are more accurate to reflect vitamin B12 functional statuses. 18,19 In our study, 27 of the 33 patients presented with high homocysteine levels, which was consistent with previous reports. Therefore, our results suggested that the level of homocysteine is a better biomarker for diagnosis of N 2 O-induced neurological disorders and a normal serum vitamin B 12 level cannot be used to exclude genuine vitamin B 12 deficiency and damage in this condition.…”
Section: Mri Findingssupporting
confidence: 93%
“…In this case, serum methylmalonic acid and homocysteine levels are more accurate to reflect vitamin B12 functional statuses. 18,19 In our study, 27 of the 33 patients presented with high homocysteine levels, which was consistent with previous reports. Therefore, our results suggested that the level of homocysteine is a better biomarker for diagnosis of N 2 O-induced neurological disorders and a normal serum vitamin B 12 level cannot be used to exclude genuine vitamin B 12 deficiency and damage in this condition.…”
Section: Mri Findingssupporting
confidence: 93%
“…Our MRI studies had a sensitivity of 44.1%. This is higher than the 14.8% (Jain et al [19]), 22.2% (Hemmer et al [11]), and 26.1% (Li et al [2]) sensitivities reported in some previous studies, but lower than the 52.8% sensitivity reported by Xiao et al [22] The following reasons may explain the low detection rate. First, the current approach may not be able to detect micro-lesions of the spinal cord.…”
Section: Discussioncontrasting
confidence: 52%
“…All the patients met the diagnostic criteria of SCD with modification: (1) clinical symptoms and signs of posterior and lateral columns or peripheral nerve impairment; (2) evidence of vitamin B 12 deficiency or clinical improvement after regular vitamin B 12 treatment in patients with normal or increased serum vitamin B 12 level; and (3) no other spinal cord or peripheral nerve disease [2]. The histories of the patients were well-documented.…”
Section: Methodsmentioning
confidence: 99%
“…Many SCD cases with typical sensory deficits similar to our patients have been reported in previous literature [1,2,6], but there are only few SCD cases showing severe motor weakness [7]. As our two patients presented low Cbl levels and typical sensory deficits of SCD, Cbl deficiency would be suggested as a main cause of SCD.…”
Section: Discussionsupporting
confidence: 79%